In Vitro Antimicrobial Activity of Five Newly Approved Antibiotics against Carbapenemase-Producing Enterobacteria-A Pilot Study in Bulgaria - Rumyana Markovska; Petya Stankova; Temenuga Stoeva; Emma Keuleyan; Kalina Mihova; Lyudmila Boyanova (MDPI AG, 2024)
To solve the problem with pan-drug resistant and extensively drug-resistant Gram-negative microbes, newly approved drugs such as ceftazidime/avibactam, cefiderocol, plazomicin, meropenem/vaborbactam, and eravacycline have been introduced in practice. The aim of the present study was to collect carbapenemase-producing clinical Enterobacterales isolates, to characterize their carbapenemase genes and clonal relatedness, and to detect their susceptibility to commonly used antimicrobials and the above-mentioned newly approved antibiotics. Sixty-four carbapenemase producers were collected in a period of one year from four Bulgarian hospitals, mainly including Klebsiella pneumoniae (89% of the isolates) and also single Proteus mirabilis, Providencia stuartii and Citrobacter freundii isolates. The main genotype was blaNDM-1 (in 61%), followed by blaKPC-2 (23%), blaVIM-1 (7.8%) and blaOXA-48 (7.8%). Many isolates showed the presence of ESBL (blaCTX-M-15/-3 in 76.6%) and AmpC (blaCMY-4 in 37.5% or blaCMY-99 in 7.8% of isolates). The most common MLST type was K. pneumoniae ST11 (57.8%), followed by ST340 (12.5%), ST258 (6.3%) and ST101 (6.3%). The isolates were highly resistant to standard-group antibiotics, except they were susceptible to tigecycline (83.1%), colistin (79.7%), fosfomycin (32.8%), and aminoglycosides (20.3-35.9%). Among the newly approved compounds, plazomicin (90.6%) and eravacycline (76.3%) showed the best activity. Susceptibility to ceftazidime/avibactam and meropenem/vaborbactam was 34.4% and 27.6%, respectively. For cefiderocol, a large discrepancy was observed between the percentages of susceptible isolates according to EUCAST susceptibility breakpoints (37.5%) and those of CLSI (71.8%), detected by the disk diffusion method. This study is the first report to show patterns of susceptibility to five newly approved antibiotics among molecularly characterized isolates in Bulgaria. The data may contribute to both the improvement of treatment of individual patients and the choice of infection control strategy and antibiotic policy.